Communes in America, 1975-2000 - Miller, Timothy, 1944- (Syracuse University Press, 2019)
Communes in America: 1975-2000 is the final volume in Miller's trilogy on the history of American intentional communities. Providing a comprehensive survey of communities during the last quarter of the twentieth century, Miller offers a detailed study of their character, scope, and evolution. Between 1975 and 2000, the American communal experience evolved dramatically in response to social and environmental challenges that confronted American society as a whole. Long-accepted social norms and institutions-family, religion, medicine, and politics-were questioned as the divorce rate increased, interest in spiritual teachings from Asia grew, and alternative medicine gained ground. Cohousing flourished as a response to an increasing sense of alienation and a need to balance community and private lives. At the same time, Americans became increasingly concerned with environmental protection and preservation of our limited resources. In the face of these social changes, communal living flourished as people sought out communities oflike-minded individuals to pursue a higher purpose.Organized topically, each chapter in the volume provides basic information about various types of communities and detailed examples of each type, from ecovillages and radical Christian communities to pagan communes and cohousing experiments. Miller also takes a step back to look at the prevalence of communal living in American life over the twentieth century. Based on exhaustive research, Miller's final volume provides an indispensable survey and guide to understanding utopianism's enduring presence in American culture.